PENELUSURAN INFORMASI WISATA EDUKASI MENGGUNAKAN MEDIA SOSIAL INSTAGRAM MELALUI HASHTAG #WISATAEDUKASIJOGJA - Maria Ana Sila Hayatri; Hendi Prasetyo (Kepariwisataan: Jurnal Ilmiah, 2021)
This study aims to find out information on educational tourism using Instagram social media through the hashtag #wisataedukasijogja. The researcher used descriptive qualitative research method with data collection techniques from literature studies and documentation. Based on the research that has been done, the researcher uses the tag or hashtag information search feature through Instagram, namely #wisataedukasijogja. Researchers found various information related to the hashtag #wisataedukasijogja, including general information on educational tourism in the Special Region of Yogyakarta. From the results of tourist visits, tourists are taught to make a product that is useful and can increase knowledge. In addition, tourists are invited to get to know the surrounding environment and various educational tourism attractions. The managers of tourist destinations offer various kinds of educational tours that are managed on the concept of indoor and outdoor with the concept of traveling to play while learning to be more varied. Tourist destination managers present various tourist attractions to children, teenagers, and adults. Other information found was the culinary offerings served by the tourist destination managers to visiting tourists as well as other educational tour package models. There are also content posts that contain schedules for organizing educational tours and educational travel experiences in the Special Region of Yogyakarta. Researchers found some other content that was not directly related to educational tourism in the Special Region of Yogyakarta. However, they include #wisataedukasijogja in their posts.Keywords: Information Search, #wisataedukasijogja, Yogyakarta Special Region